Organizational structure characteristics' influences on international purchasing performance in different purchasing locations. Issue 4 (October 2019) - Richter, Nicole Franziska; Schlaegel, Christopher; Midgley, David F.; Tressin, Tabea
Abstract: This study contributes to the understanding of how firms should structure their purchasing organization to improve their performance. While the research into structural characteristics' impacts on purchasing performance is evolving, it is still incomplete, especially concerning the contingencies on different purchasing environments. Drawing on ideas from the organizational information processing and contingency approaches as well as the international business literature, the present study proposes a model in which three key organizational structure characteristics – centralization, standardization, and specialization – are associated with purchasing performance. This study posits that the relationships are contingent on a purchasing location's formal and informal institutional context. Based on a sample of 195 German manufacturers, the model is empirically tested using structural equation modeling. The findings support the relevance of organizational structure characteristics for international purchasing and firm performance and they also support the notion that the effects are contingent on the purchasing location's institutional context. Highlights: Examine the organizational structure-international purchasing performance link. Analysis of the moderating role of purchasing locations' institutional environments. Data of 195 German manufacturers with 37 different purchasing locations. Centralization and specialization positively influence purchasing performance. Links for standardization and specialization are contingent on purchasing location.